2020
DOI: 10.21037/atm.2020.02.142
|View full text |Cite
|
Sign up to set email alerts
|

Non-disruptive mutation in TP53 DNA-binding domain is a beneficial factor of esophageal squamous cell carcinoma

Abstract: Background: TP53 is frequently altered in esophageal squamous cell carcinoma (ESCC). However, the landscape of TP53 mutation and its effects on patients remain controversial.Methods: Somatic mutations of TP53 in 161 patients with resectable ESCC were identified by nextgeneration sequencing (NGS) and verified by immunohistochemistry (IHC). Patients were stratified into seven TP53 mutations, and depending on the extent of the effect on the encoded protein, it was divided into "disruptive" and "non-disruptive" ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…The mutation rate of TP53 in tumor samples was only 58.49%, which is lower than reported mutation frequency, mainly due to panel coverage (not all exons of TP53 were included) and small sample size. The mutational spectrum of TP53 is diverse in human cancers, apart from the "hotspot mutations" (23). The reported mutation rate of ESCC varies in different studies, ranging from 20% to 93%, which is mainly determined according to the sequencing panel coverage, methods used, and tumor stage (23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mutation rate of TP53 in tumor samples was only 58.49%, which is lower than reported mutation frequency, mainly due to panel coverage (not all exons of TP53 were included) and small sample size. The mutational spectrum of TP53 is diverse in human cancers, apart from the "hotspot mutations" (23). The reported mutation rate of ESCC varies in different studies, ranging from 20% to 93%, which is mainly determined according to the sequencing panel coverage, methods used, and tumor stage (23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…The mutational spectrum of TP53 is diverse in human cancers, apart from the "hotspot mutations" (23). The reported mutation rate of ESCC varies in different studies, ranging from 20% to 93%, which is mainly determined according to the sequencing panel coverage, methods used, and tumor stage (23)(24)(25)(26)(27)(28)(29). We identified more variants in pre-surgical cfDNA specimens compared with tumors, indicating spatial intratumoral heterogeneity in ESCC; Hao et al also illustrated this (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant differences were assessed between the two groups, yet the shorter PFS subgroup revealed a TMB higher than eight. One could guess that an increased TMB is correlated with the existence of resistance pathways, as previous reports suggested [94]. Furthermore, among overall clinical studies, EGFR-TKIs appeared to have less activity in 67 patients harboring concomitant TP53 gene mutations.…”
Section: Tp53 Pten Pik3ca Cdkn2a and Rb1mentioning
confidence: 89%
“…Mutation in TP53 gene have been divided into disruptive mutations and non-disruptive ones considering the loss of function of p53 protein. Specifically, disruptive mutations produce a complete loss of function of p53, while non-disruptive alterations result in conservative mutations or non-conservative mutations (excepting stop codons) outside the L2-L3 region [91,[93][94][95]. Comprehensively, the systematic literature review identified a total of 11 reports evaluating the TP53 status in EGFR-mutant patients with lung adenocarcinoma.…”
Section: Tp53 Pten Pik3ca Cdkn2a and Rb1mentioning
confidence: 99%